Obtención de briquetas a partir de una mezcla de cascarilla de arroz y cisco de carboneria en la región de San Martín - Tapia Bautista, Percy (2005)
The present investigation work has like object, to take advantage of the husk of rice in combination. with coalyard cisco, using as ligante, clay, to obtain a combustible briquette, of low cos and of high to be abla to caloric guided to the domestic or industrial usel. It intended five relationships of mixtures in proportions volumétricas of 1:0, 1:1, 2:1, 3: 1 and 4: 1; of coalyard cisco and husk of rice respectively; using three ligante levels: 8º/o, 12% y 15% in functionto the weight of the dry mixture, that which generates fifteen treatments.of these treatments, the mixture 1: 1 onecould not obtain lower any ligante level; decreasing then to twelve experimental treatments. The husk of rice was used in its natural state and its content of humidity was of 8°/o.on theother hand el coalyard cisco, had a content of humidity of 4°/o and the humidity of the clay was of 16.16%. It has benn made a sifted to the coalyard cisco with mesh of 114", because in preliminary evaluations, it has hindered the obtaining of the briquettes. The achieved experimental units have cylindrical form of fifteen centimeters of high for fifteen centimeters of diameter; they possess 22 holes or perforations that facilitate their combustión. The evaluated properties constitute the mechanical resístance at the compression and the time of combustión, parameters that have allowed to define the proportion of mixture ideal between husk ofrice and coalyard cisco this way, the level of more appropriate ligante. For this determination, a design was applied with factorial arrangement of 4A x 3B, selecting as the ideal to the treatment that contains three parts of coalyard cisco and a part. Of husk of rice, with a lvel of ligante of 12%. The samples of the selected treatmen, present as charateristic: a weight average of 2450.42 gr., 3.64% of humidity, 9.75 Kg/cm2 of resistance to the compresión, 10.38 hours of continuous combustion, it generates a caloric power of 4,119.38 Kcal/Kg and a cost of production of s/ O. 75 for briquette. When carryng out a cost análisis and of being able to caloric, with that of the conventional fuels used in the such means as: quinilla colorada, chucchumbo firewood, espintana firewood, kerosene and gas propane was 'determined as the fuel that possesses more advantages on the other conventional fuels, by its low cost and time of continuous energy that this it toasts.